Twist and chord optimization using the linearization method on the taper blade of a micro-horizontal axis wind turbineTwist and chord optimization using the linearization method on the taper blade of a micro-horizontal axis wind turbine - Syaukani, Muhammad; Aryadi, Anugrah Wahyu; Arirohman, Ilham Dwi; Sofyan, Sarwo Edhy; Bahar, Aditiya Harjon; Sabar, Sabar (Politeknik Negeri Lhokseumawe, 2024)
The research aims to optimize the geometry of taper blade profiles for the Horizontal Axis Wind Turbine (HAWT) to improve aerodynamic performance and minimize fabrication complexity. The study used blade linearization as an optimization method for identifying a desirable twist (β) and chord (Cr). This approach enhances accuracy and boosts computational efficiency. It simplifies the optimization process by reducing complexity. In contrast, traditional nonlinear methods are slower and more resource-intensive due to complex aerodynamic interactions. The best β and Cr distributions were found by linearization with elements 1 and 10 of the blade length and positions 5%, 15%, 25%, 35%, 45%, 55%, 65%, 75%, 85, and 95% of the blade elements. The linearization results were used to determine the optimum performance of the HAWT design using simulation. The optimal blades for HAWT were fabricated and their performance evaluated under real wind conditions. The linearization of the 45% twist and chord of elements 1 and 10 provided the best blade shape. Optimized twist and chord yielded HAWT performance with the Cp of 45% to 47% at rotational speeds of 200–900 rpm and wind speeds of 2–10 m/s. Twist and chord optimization increased the Cp from 39.71% to 46.43% with a rotational speed of 550 rpm at a wind speed of 6 m/s, as well as the maximum mechanical power from 424.28 watts to 500.35 watts at a wind speed of 10 m/s. The result from real wind conditions showed that manufactured HWAT produced an average electrical power of 294.19 watts at a rotational speed of 590.66 rpm. These results demonstrate that the optimized design approach presents a close match and is still reasonable in comparison to practical conditions.